The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/0103-8478cr20140050
|View full text |Cite
|
Sign up to set email alerts
|

Growth and production of ornamental sunflower grown in the field in response to application of humic acids

Abstract: The humic acid fraction of organic matter has a stimulating effect on the growth and development of ornamental plants. This study investigated the response in growth and yield of field-grown ornamental sunflower (Helianthus annuus L.) to the seed treatment with humic acids. The experiment was arrangedin a randomized block design with three replications. Sunflower seeds were soaked in solutions of 0, 10, 20, 30, and 40mmol L -1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…Somados aos efeitos dos ácidos húmicos no enraizamento, ressaltam-se, também, os efeitos estimulantes na parte aérea, como incrementos do acúmulo de nutrientes foliares (Vaughan & Malcolm, 1979;Chen & Avaid, 1990;Chen et al, 2004;Eyheraguibel et al, 2008;Baldotto et al, 2009b;Mora et al, 2010;Jannin et al, 2012), da biossíntese de clorofilas (Tejada & Gonzalez, 2003;Ferrara & Brunetti, 2008;Baldotto et al, 2009b;Ameri & Tehranifar 2012;Jannin et al, 2012;Ahmad et al, 2013), da biossíntese de carotenoides (Tejada & Gonzalez, 2003;Baldotto et al, 2009b), da presença de cloroplastos (Jannin et al, 2012) e do processo fotossintético (Ameri & Tehranifar 2012;Jannin et al, 2012). Todos esses fatores resultam em incrementos da biomassa vegetal (Atiyeh et al, 2002;Tejada & Gonzalez, 2003;Baldotto et al, 2009b;Wangen et al, 2013;, da produção de flores (Arancon et al, 2006;Baldotto & Baldotto, 2014a), de frutos (Arancon et al, 2006;Lima et al, 2011) e de sementes (Baldotto & Baldotto, 2014c).…”
Section: Bioatividade Dos áCidos Húmicosunclassified
See 1 more Smart Citation
“…Somados aos efeitos dos ácidos húmicos no enraizamento, ressaltam-se, também, os efeitos estimulantes na parte aérea, como incrementos do acúmulo de nutrientes foliares (Vaughan & Malcolm, 1979;Chen & Avaid, 1990;Chen et al, 2004;Eyheraguibel et al, 2008;Baldotto et al, 2009b;Mora et al, 2010;Jannin et al, 2012), da biossíntese de clorofilas (Tejada & Gonzalez, 2003;Ferrara & Brunetti, 2008;Baldotto et al, 2009b;Ameri & Tehranifar 2012;Jannin et al, 2012;Ahmad et al, 2013), da biossíntese de carotenoides (Tejada & Gonzalez, 2003;Baldotto et al, 2009b), da presença de cloroplastos (Jannin et al, 2012) e do processo fotossintético (Ameri & Tehranifar 2012;Jannin et al, 2012). Todos esses fatores resultam em incrementos da biomassa vegetal (Atiyeh et al, 2002;Tejada & Gonzalez, 2003;Baldotto et al, 2009b;Wangen et al, 2013;, da produção de flores (Arancon et al, 2006;Baldotto & Baldotto, 2014a), de frutos (Arancon et al, 2006;Lima et al, 2011) e de sementes (Baldotto & Baldotto, 2014c).…”
Section: Bioatividade Dos áCidos Húmicosunclassified
“…O potencial de uso de ácidos húmicos na conservação e manejo dos ecossistemas naturais e agrários é vasto e promissor, incluindo, principalmente, a promoção do crescimento e desenvolvimento de plantas e o aumento da produção de flores, frutos e sementes (Arancon et al, 2006;Baldotto & Baldotto, 2014a, b). Estudos recentes demonstram também o potencial de uso de ácidos húmicos no aumento da eficiência da adubação mineral (Pinto et al, 2008;Ahmad et al, 2013;Baldotto et al, 2011c, Baldotto & Baldotto, 2014a e na formulação de inoculantes e biofertilizantes (Marques Jr. et al, 2008;Baldotto et al, 2010b;Rodrigues et al, 2014). Baldotto et al (2011a), por exemplo, demonstraram, de forma inovadora, o potencial de uso de ácidos húmicos (9,3 mmol L -1 de C, na forma de ácidos húmicos de vermicomposto) combinados com ácido cítrico (0,005 mmol L -1 ), no aumento da eficiência da adubação foliar de abacaxizeiro com fosfato de rocha (fosfato de Araxá), observando aumento dos conteúdos foliares de N, P, K, Ca e Mg e do crescimento da parte aérea das mudas.…”
Section: Bioatividade Dos áCidos Húmicosunclassified
“…Similar results were found by Mota et al (2007) and Pirola et al (2015) whom noticed increments in plant height when increasing the dosage of the applied treatment. This is due to the fact that these nutrients are involved in cell elongation and division, and also because they are fundamental constituents of organelles and compounds involved in photosynthesis, especially nitrogen, thus resulting in response of stem length (BARBOSA et al, 1999;RODRIGUES et al, 2008;CASTRO et al, 2011;BALDOTTO and BALDOTTO, 2015).…”
Section: Dry Matter Of Leaves Stems and Length Of Stemsmentioning
confidence: 99%
“…Sarwar et al (2019), Rady et al (2020), andAbd El-Mageed et al (2020) reported that the exogenous-applied nutrients induced heat and drought stress tolerance in cotton, wheat, and maize crops, respectively, by modulating their morpho-physiological characteristics. HA as a multi-nutrient fertilizer or soil conditioner can mend soil hydro-physical characteristics, nutrients uptake and consequently improve photosynthesis, growth, and yield in normal and stressed plants (Baldotto and Baldotto 2015;Hemida et al 2017). Exogenous addition of HA as an eco-friendly organic fertilizer to the soil has both direct and indirect positive influences on crop plants (Rady et al 2016;Belal et al 2019).…”
Section: Introductionmentioning
confidence: 99%